(untitled) (Práxis Educativa, 2022)
Considering the educational dimension of porn movies, we describe and analyze in this text the pedagogy of masculinization in the post-critical perspective of the curriculum. We understand that the curriculum is not restricted to school subjects, but consists of different spaces and cultural artifacts. The methodology used in the investigation articulated elements of netnography and analysis of the Foucaultian-inspired discourse of four pages of the cyberspace. In the production of information, we named a heterogeneous set of sayings, videos and images published on these bareback curriculum sites. In this article our analysis focus is a set of porn videos. The argument developed is that in porn videos disclosed in the bareback curriculum there is a pedagogy of masculinization, which acts through specific techniques, in order to disseminate, teach and prescribe a certain way of being a young bareback man, the one who has his conduct prescribed by gender norms, which act in conjunction with sexuality. Keywords: Gender. Pedagogy. Porn.